2017
DOI: 10.29252/ijrm.15.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Administration of high dose of methamphetamine has detrimental effects on sperm parameters and DNA integrity in mice

Abstract: Background:Methamphetamine (MA) was shown to have harmful effects on male reproductive system. Objective:To investigate probable effects of daily administration of MA on sperm parameters and chromatin/DNA integrity in mouse.Material and Methods:Thirty-five NMRI male mice were divided into five groups including low, medium, and high dosage groups which were injected intraperitoneally with 4, 8 and 15 mg/kg/day for 35 days, respectively. Normal saline was injected in sham group and no medications were used in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…In accordance with our findings, the morphological deformities of sperm in the tail region of hypothyroid and hyperthyroid men have been reported [37]. Moreover, inconsistent with our results, several experiments have shown that administration of methamphetamine, gold nanoparticles, and acrylamide leads to a decrease in the sperm normal morphology [22,26,31]. To our knowledge, the present study was the first report that showed the relationship between the abnormal sperm chromatin quality and hypothyroidism.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In accordance with our findings, the morphological deformities of sperm in the tail region of hypothyroid and hyperthyroid men have been reported [37]. Moreover, inconsistent with our results, several experiments have shown that administration of methamphetamine, gold nanoparticles, and acrylamide leads to a decrease in the sperm normal morphology [22,26,31]. To our knowledge, the present study was the first report that showed the relationship between the abnormal sperm chromatin quality and hypothyroidism.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, the slides were cleared with xylene and mounted with Entellan (Merck, Germany). After imaging with Olympus (BX51, Japan) light microscope at ×1000 magnification objective lenses (UPlan FI, Japan), normal and abnormal forms of sperm morphology were determined [31].…”
Section: Morphological Evaluation Of Spermmentioning
confidence: 99%
See 3 more Smart Citations